2004
DOI: 10.1159/000077817
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Hippocampal and White Matter Alterations in Mild Cognitive Impairment: A Diffusion Tensor Imaging Study

Abstract: Mild cognitive impairment (MCI) is considered to be a transitional stage between normal aging and dementia. In Alzheimer’s disease (AD), white matter structural pathology is due to Wallerian degeneration and central angiopathy. However, in MCI patients, the presence and extent of white matter alterations as a possible correlate of impaired memory function and as predictor of subsequent progression to AD is not clarified yet. Diffusion tensor imaging (DTI) reveals the ultrastructural integrity of cerebral white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
205
5
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(250 citation statements)
references
References 46 publications
34
205
5
6
Order By: Relevance
“…The involvement of this tract as well as the CC, fornix, perforant path, and temporal WM is consistent with previous findings from DTI studies that reported diffusivity increases or anisotropy decreases in the same set of WM areas (Fellgiebel et al, 2004;Medina et al, 2006;Xie et al, 2006;Huang et al, 2007;Teipel et al, 2007;Zhang et al, 2007). Atrophy of the CC and perforant path have also already been highlighted in previous VBM studies of AD (Chaim et al, 2007) and MCI (Stoub et al, 2006), respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The involvement of this tract as well as the CC, fornix, perforant path, and temporal WM is consistent with previous findings from DTI studies that reported diffusivity increases or anisotropy decreases in the same set of WM areas (Fellgiebel et al, 2004;Medina et al, 2006;Xie et al, 2006;Huang et al, 2007;Teipel et al, 2007;Zhang et al, 2007). Atrophy of the CC and perforant path have also already been highlighted in previous VBM studies of AD (Chaim et al, 2007) and MCI (Stoub et al, 2006), respectively.…”
Section: Discussionsupporting
confidence: 90%
“…5,6 In addition, diffusion tensor imaging showed WM damage not only inside but also outside the temporal lobe in patients with MCI. 28 In this MTI study, we were able to expand on these former studies because we showed widespread WM damage in all lobes of patients with both MCI and AD, applying volumetric analysis. We hypothesize that the observed WM changes are caused by chronic hypoperfusion based on cerebral small vessel disease.…”
Section: Discussionmentioning
confidence: 92%
“…5,28 However, in all the previous studies investigating the lobar distribution of MTR changes in patients with MCI and AD, GM and WM were taken together. [13][14][15] Therefore, it remained unclear whether the widespread MTR changes found in AD and MCI were attributable to damage in the GM only.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DTI has been considered to be sensitive in exploring hippocampal changes [36] . For example, Fellgiebel and colleagues have demonstrated that aMCI patients show increased MD and decreased FA in the left hippocampus, with no significant changes in the right hippocampus [37] . However, Mulle and colleagues evaluated the cross-sectional discriminative accuracy of hippocampal volume and DTI measures with regard to aMCI and demonstrated increased MD and reduced FA in the bilateral hippocampus, particularly on the left side [38] .…”
Section: Patientsmentioning
confidence: 99%